2016
DOI: 10.1080/09540121.2016.1164806
|View full text |Cite
|
Sign up to set email alerts
|

Men “missing” from population-based HIV testing: insights from qualitative research

Abstract: Men’s uptake of HIV testing is critical to the success of “test and treat” strategies in generalized epidemics. This study sought to identify cultural factors and community processes that influence men’s HIV testing uptake in the baseline year of an ongoing test-and-treat trial among 334,479 persons in eastern Africa (SEARCH, NCT#01864603). Data were collected using participant observation at mobile community health campaigns (CHCs) (n = 28); focus group discussions (n = 8 groups) with CHC participants; and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
154
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(167 citation statements)
references
References 16 publications
10
154
3
Order By: Relevance
“…Besides characterizing the trial populations with standard socio‐demographic information, these trials also collect experiences and perceptions of a sample of trial participants, community members and services providers. Such qualitative research provides evidence to understand the acceptability of the UTT strategies by the general population 29, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Besides characterizing the trial populations with standard socio‐demographic information, these trials also collect experiences and perceptions of a sample of trial participants, community members and services providers. Such qualitative research provides evidence to understand the acceptability of the UTT strategies by the general population 29, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research from Tanzania found that men living apart from their wives did not report more extramarital sex than men who co‐resided with their wives, but the opposite was true for women, among whom those living apart reported extramarital sex more often . Normative masculinities in these settings are such that men's extramarital affairs, while often leading to marital strife, are common and even valorised . In Kenya, funerals are multi‐day gatherings of friends and family at the home of the deceased, accompanied by music and dancing; these are also occasions in which casual, transactional unprotected sex is common .…”
Section: Discussionmentioning
confidence: 99%
“…The streamlined care system employed by the clinics, which decreased the frequency and improved the efficiency of visits, could have particularly benefited men by reducing any disruption to employment or other work. In these communities in rural East Africa a large proportion of the men work as farmers or fishermen, which requires them to be away from their communities for extended periods, and has been a demonstrated to deter men from to facility-based testing[35]. Men did require additional effort through retention tracking to stay in care, and may have benefited from this individualized outreach.…”
Section: Discussionmentioning
confidence: 99%